An Autophagy-Related Gene Signature Associated With Clinical Prognosis and Immune Microenvironment in Gliomas - Xu, Yang; Li, Renpeng; Li, Xiaoxia; Dong, Naijun; Wu, Di; Hou, Lin; Yin, Kan; Zhao, Chunhua (Frontiers in Oncology, 2020)
Gliomas is one of the leading causes of death from cancer and autophagy-related genes plays an important role in glioma occurrence, progression and treatment. In this study, gene expression profiles and clinical data of glioma patients were downloaded from The Cancer Genome Atlas database and Chinese Glioma Genome Atlas, respectively. Autophagy-related genes (ARGs) is obtained from the Human Autophagy Database. We analyzed the expression of ARGs in glioma and found that 73 ARGs were differentially expressed in tumor and normal tissues. Univariate Cox regression analysis was used to identify prognostic differentially expressed ARGs (PDEARG). LASSO and multivariate Cox regression analyses were performed on PDEARG to determine the risk genes. Consequently, BRIC5, NFE2L2, GABARAP, IKBKE, BID, MAPK3, FKBP1B, MAPK8IP1, PRKCQ, CX3CL1, NPC1, HSP90AB1, DAPK2, SUPT20H and PTEN were selected to establish the prognostic risk score model in TCGA and CGGA cohorts. Moreover, this model accurately stratified patients with different survival outcomes. The autophagy-related signature was also appraised as an independent prognostic factor. We also constructed a prognostic nomogram including risk score, age, gender, WHO grade, IDH mutation status and 1p/19q codeletion status, and the calibration plots showed its great prognostic performance. Finally, correlation analysis suggested that the autophagy-related gene signature also played an essential role in the tumor immune microenvironment. Overall, we constructed and verified a novel autophagy-related signature which was tightly associated with the tumor immune microenvironment and could serve as an independent prognostic biomarker in gliomas.